Social Assessment of Area of Influence : Togolok Deposit - Oxus International (World Bank, Washington, DC, 2014)
This report presents findings of social research conducted in the Akshiyrak Aiyl Okmotu of Kyrgyzstan (located in Jeti-Oguz raion, Issykkul province). The aim of the research was to study the current social situation in Akshiyrak Aiyl Okmotu and the potential social, economic, and ecological impact of the construction and operation of the mine at the Togolok gold deposit. The findings of the research will be used by the World Bank for assisting and advising the Government of the Kyrgyz Republic on conducting the tender for the Togolok gold deposit. Past experiences have demonstrated that mining can have several positive and negative impacts on the communities surrounding the mine. This research project was intended to offer a partial insight into how the presence of a gold mine may impact Akshiyrak. To fulfill the aim of the research, firstly, a desk study was conducted which looked at the community involvement in the mining sector in Kyrgyzstan including the relevant legislation. Secondly, fieldwork was undertaken in the Akshiyrak Aiyl Okmotu where interviews and focus groups with key actors and residents of the community were held. Finally, the findings of the research were presented by the research team to representatives of the Akshiyrak community in a validation workshop and the findings were adjusted accordingly.